2010
DOI: 10.5001/omj.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Glucose to Leptin Ratio as a New Diagnostic Marker in Patients with Diabetes Mellitus

Abstract: Overall, the glucose/leptin ratio can be used in addition to glucose/insulin ratio, Quantitative Insulin-Sensitivity Check Index, and Homeostasis Model Assessment to accurately assess insulin resistance in subjects with hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Additionally, we measured leptin levels since it has been reported by some groups that InsRes is accompanied by leptin resistance, and that the ratio of both hormones can be used as a parameter for measuring metabolic alterations in humans and rodents. 28 We found a significant increase in leptin levels in the HFFD rats as compared with controls (94.5%, Po0.001) as well as a positive correlation bet-ween the two hormones levels (r ¼ 0.6697, P ¼ 0.0280) ( Figure 1C). These data indicate that HFFD-fed rats develop systemic InsRes and elevated levels of leptin, which has also been associated with the development of obesity and InsRes.…”
Section: Short-term High-fat-and-fructose Diet Feeding Induces Obesitmentioning
confidence: 65%
“…Additionally, we measured leptin levels since it has been reported by some groups that InsRes is accompanied by leptin resistance, and that the ratio of both hormones can be used as a parameter for measuring metabolic alterations in humans and rodents. 28 We found a significant increase in leptin levels in the HFFD rats as compared with controls (94.5%, Po0.001) as well as a positive correlation bet-ween the two hormones levels (r ¼ 0.6697, P ¼ 0.0280) ( Figure 1C). These data indicate that HFFD-fed rats develop systemic InsRes and elevated levels of leptin, which has also been associated with the development of obesity and InsRes.…”
Section: Short-term High-fat-and-fructose Diet Feeding Induces Obesitmentioning
confidence: 65%
“…This ratio was negatively correlated with SBP, DBP, MAP, and HOMA-IR in men. One study reported that the fasting Glc/I ratio is an appropriate index of insulin sensitivity, but it becomes apparent only when fasting glucose levels are abnormal (39). Similarly, another study reported that it is a weak insulin sensitivity index and is probably similar to 1/insulin in nondiabetic subjects (40).…”
Section: Discussionmentioning
confidence: 99%
“…Migraine sufferers often report cravings for food high in refined sugar and then a migraine develops later [23]. Lower G/I ratio [2,33] and higher I/C ratio [15] depict higher degrees of insulin resistance. In the present study the consumption of sucrose resulted in an immediate decrease in the G/I ratio and increase in I/C ratio in all participants.…”
Section: Migrainementioning
confidence: 98%